Atheism remix: a Christian confronts the new atheists - Mohler, R. Albert, Jr. (Crossway Books, 2008)
The new atheism and the endgame of secularism -- The new atheism and the assault on theism -- The new atheism and the defense of theism -- The new atheism and the future of Christianity